The application of SCADA systems on wrapping machines using plc and wonderware intouch in the automotive manufacturing industry - Ardi, Syahril; Ningsih, Nur Dewi; Hidayat, Muhammad; Fairus, Sirin; Ponco, Agus (Jurnal Pendidikan Teknologi dan Kejuruan, 2024)
In this paper, the application of SCADA systems in the automotive product packaging process has been carried out. At an Automotive Manufacturing Industrial Company that produces tires and tubes specifically for two-wheeled vehicles. In making marketable tires, there are various processes that must be gone through, namely: mixing, extrusion, bead wire, calendaring, bias cutting, manufacturing, curing, final inspection, and wrapping. The wrapping process is the process of packaging the outer tire, with the work process of wrapping the outer tire using a predetermined plastic. In the wrapping process there is a process of collecting counter result data manually using a check sheet by the machine operator. The machine operator takes the counter data displayed on the panel of each machine. After that, the data is collected by the foreman at the end of the shift, then the data is recapitulated and entered manually into the recap data for the accomplishment of the wrapping process by the foreman. This process is considered less efficient because it is quite time-consuming, and the level of human error that may occur is quite high. Therefore, we designed a SCADA system for the wrapping machine using the Wonderware Intouch 10.6 application. In this case, we use data communication between a PC (Personal Computer) which contains the Wonderware application program and Microsoft SQL Server with a Mitsubishi Q02H PLC (Programmable Logic Controller) via the QJ71E71-100 ethernet module, and the cc-link module as a remote Input-output module. The machine counter results data is stored in the Microsoft SQL Server database. The process of saving monitoring data from Wonderware Intouch to Microsoft SQL Server is done by creating a table in the Microsoft SQL Server database, adding ODBC (Open Database Connectivity) according to the database that has been created, and creating a bindlist on Wonderware Intouch. This SCADA system was developed for high accuracy, eliminating the manual process of inputting counter data results, and it can monitor production results automatically from a PC both in the interface and data acquisition recorded in Microsoft SQL Server.